The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.annonc.2020.04.470
|View full text |Cite
|
Sign up to set email alerts
|

P-385 A phase 1/2 study of combination therapy of ivaltinostat, gemcitabine, and erlotinib in patients with unresectable, locally advanced and metastatic pancreatic adenocarcinoma

Abstract: individuals prognostic tests identified overall, -/+ HDAA, groups with median survivals of 15.5 -24 mos. HDAA did not significantly reduce survival. Severe AEs range from 0-< 5% in HDAA groups. Favorable S trends were attributable to Taxanes, % females and A.L.A.N. cell ratios. The latter are putative surrogate markers of immune function. Unexpectedly, contrary to clinical characteristics, and referring physician expectations, the majority of patients had up to 75% favorable prognostic tests. Conclusion:All co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A preclinical study by Lee et al showed growth inhibition and anti-neoplastic effects in gemcitabine-resistant pancreatic cancer cells, following treatment with CG200745 plus gemcitabine and erlotinib (an EGFR inhibitor) in vitro and in vivo [193]. One phase I/II study explored the clinical effects of this combination (CG200745 plus gemcitabine and erlotinib) in 34 patients with unresectable, locally advanced/metastatic pancreatic cancer (NCT02737228) [194]. Part I consisted of 10 patients and set out to outline the maximum tolerated dose of CG200745, with results determining this to be 250 mg/m 2 .…”
Section: Cg200745 (Ivaltinostat)mentioning
confidence: 99%
“…A preclinical study by Lee et al showed growth inhibition and anti-neoplastic effects in gemcitabine-resistant pancreatic cancer cells, following treatment with CG200745 plus gemcitabine and erlotinib (an EGFR inhibitor) in vitro and in vivo [193]. One phase I/II study explored the clinical effects of this combination (CG200745 plus gemcitabine and erlotinib) in 34 patients with unresectable, locally advanced/metastatic pancreatic cancer (NCT02737228) [194]. Part I consisted of 10 patients and set out to outline the maximum tolerated dose of CG200745, with results determining this to be 250 mg/m 2 .…”
Section: Cg200745 (Ivaltinostat)mentioning
confidence: 99%